Isogeometric spline reconstruction of plane curves - Nazarenko, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish conditions for the isogeometric reconstruction of plane curves by using parabolic and cubic parametric splines of minimal defect.